A comparative study of carbon dioxide absorption capacity of seven urban forest plant species of Banda Aceh, Indonesia - Malahayati Daud; Betty Mauliya Bustam; BASTIAN ARIFIN (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Daud M, Bustam BM, Arifin B. 2019. A comparative study of carbon dioxide absorption capacity of seven urban forest plant species of Banda Aceh, Indonesia. Biodiversitas 20: 3372-3379. Global warming has been a major issue affecting all parts of the world in recent years. One method of reducing the impact of global warming is through supporting the green open space. The city government of Banda Aceh, Indonesia has targetted as much as 30% of its area to the formation of green open space. The BNI urban forest is one example of the green open spaces in Banda Aceh. This research was conducted to know the carbon dioxide absorption capacity in seven selected tree species found in the urban forest. The method that has been applied was the explorative survey method with purposive sampling. The data were analyzed using linear regression and correlation analysis. The results showed that the highest ability of carbon dioxide absorption per leaf per hour was found in the Terminalia catappa (0.511 g/leaf/hour) and the lowest was found in the Calophyllum inophyllum (0.056 g/leaf/hour). While the highest carbon dioxide absorption per tree per hour was found in Pterocarpus indicus (4,642,293 g/tree/hour) and the lowest was found in Calophyllum inophyllum (162,640 g/tree/hour). The results of linear regression analysis showed that there was no strong correlation and no significant effect between leaf surface area and mass of carbohydrate, to capacity of carbon dioxide absorption in urban forest plants.